(untitled) (LACCEI, 2024)
Currently in the market there are diverse types of energy dissipation devices that are used both for installation in new structures, and in the reinforcement of some that are at risk of causing an accident caused by a large earthquake. The article that will be presented below has the purpose of analyzing buildings with energy dissipators, the response they generate in the face of a large-magnitude earthquake and the recommendations on seismic design to develop structural reinforcement strategies for old and damaged buildings that need it. The first part deals with the types of energy devices that are most used and efficient on the market. Subsequently, the application and performance for the design of buildings with dissipators are mentioned, in addition to the improvement obtained by placing it in deteriorated structures or on the verge of collapsing. On the other hand, the purpose of the research is to generate interest so that more people know about energy dissipators and how they can minimize damage to buildings and deteriorated structures in the event of an earthquake.